End-organ consequences of the Fontan operation: liver fibrosis, protein-losing enteropathy and plastic bronchitis. (9th January 2014) - Rychik, Jack; Goldberg, David; Rand, Elizabeth; Semeao, Edisio; Russo, Pierre; Dori, Yoav; Dodds, Kathryn
Abstract The Fontan operation, although part of a life-saving surgical strategy, manifests a variety of end-organ complications and unique morbidities that are being recognised with increasing frequency as patients survive into their second and third decades of life and beyond. Liver fibrosis, protein-losing enteropathy and plastic bronchitis are consequences of a complex physiology involving circulatory insufficiency, inflammation and lymphatic derangement. These conditions are manifest in a chronic, indolent state. Management strategies are emerging, which shed some light on the origins of these complications. A better characterisation of the end-organ consequences of the Fontan circulation is necessary, which can then allow for development of specific methods for treatment. Ideally, the goal is to establish systematic strategies that might reduce or eliminate the development of these potentially life-threatening challenges.